Reassessing the Foundation of Transaction Cost Economics: A Systematic Literature Review (2022–2025) - Fatihatussharifah; Sambas Ade Kesuma (Locus Journal of Academic Literature Review, 2025)
This systematic literature review (SLR) reassesses the theoretical foundation and contemporary relevance of Transaction Cost Economics (TCE) by examining 64 articles published between 2022 and 2025. Grounded in the classic works of Coase (1937) and Williamson (1975, 1985), TCE analyzes how organizations choose governance structures that minimize transaction costs driven by bounded rationality, uncertainty, and opportunism. The findings show that TCE continues to be applied across various disciplines, including supply chain management, information systems, organizational governance, and public policy. Recent research reveals a shift from a strictly economic perspective to a more dynamic, multidisciplinary approach. Many contemporary studies combine TCE with complementary theories such as the Resource-Based View (RBV), Agency Theory, and Institutional Theory to enhance its explanatory strength and connect cost efficiency with strategic capabilities. Traditional variablesasset specificity, uncertainty, and opportunism remain central, but scholars increasingly include modern variables such as trust, digital capability, and technological interdependence. These additions reflect the growing complexity of digital and interconnected environments. Several research gaps emerge, particularly related to digital industries, public sector governance, sustainability-oriented collaborations, and cross-country comparisons. Overall, this SLR confirms that while TCE remains highly relevant, it must continue evolving to address the challenges of modern, rapidly digitalizing economic contexts.